2014
DOI: 10.1111/ajo.12242
|View full text |Cite
|
Sign up to set email alerts
|

Can anyone screen for deep infiltrating endometriosis with transvaginal ultrasound?

Abstract: After one week of DIE-TVUS training, competency can be achieved within forty procedures, allowing diagnosis of DIE with similar diagnostic accuracy as reported by centres of excellence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 24 publications
0
52
2
Order By: Relevance
“…They also found that interpretation of the sliding sign at the retrocervix was better than that at the posterior upper uterine fundus. Experienced operators who have performed in excess of 2500 scans reach proficiency in performing the sliding sign maneuver and detecting POD obliteration after approximately 40 examinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that interpretation of the sliding sign at the retrocervix was better than that at the posterior upper uterine fundus. Experienced operators who have performed in excess of 2500 scans reach proficiency in performing the sliding sign maneuver and detecting POD obliteration after approximately 40 examinations.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to detection of POD obliteration, experienced operators who have performed in excess of 2500 scans reach proficiency in the detection of rectal DIE nodules using TVS after approximately 40 examinations. With the exception of DIE affecting the RVS, TVS in the hands of well‐trained staff is a highly accurate and reproducible method for non‐invasive diagnosis of DIE.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the full text of the remaining 43 articles. Twenty‐four studies were discarded because they did not meet the inclusion criteria and the remaining 19 studies were included in the review and meta‐analysis. No additional relevant studies were found from references cited in the papers included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…state that TVS techniques fail to reduce the gap between the ‘brilliant results’ achieved by investigators proposing these techniques and those ‘less satisfactory’ collected during routine clinical practice owing to poor repeatability, high interoperator variability, and inadequate period of the training that is necessary to achieve sufficient levels of expertise. Others, however, have found that with only 1 week of DIE‐TVS training, competency can be achieved within 40 procedures, enabling diagnosis of DIE with similar diagnostic accuracy to that reported by centers of excellence. Eisenberg et al .…”
Section: Introductionmentioning
confidence: 97%